If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6c + -8 + -2c = 16 Reorder the terms: -8 + 6c + -2c = 16 Combine like terms: 6c + -2c = 4c -8 + 4c = 16 Solving -8 + 4c = 16 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 4c = 16 + 8 Combine like terms: -8 + 8 = 0 0 + 4c = 16 + 8 4c = 16 + 8 Combine like terms: 16 + 8 = 24 4c = 24 Divide each side by '4'. c = 6 Simplifying c = 6
| 9-w=19 | | (5x)(x)=45 | | 9n-27=-33+8n | | 2a+3=9+4a | | 5-3t=32 | | x-0.6=8.11 | | 6a+7=25 | | x+3y=0 | | 29r=174 | | 24y=48 | | 5w+9.9=4.8w | | 4p+5=19 | | 2x^2-15x-14+3x=0 | | -16t^2+520=y | | x+10=-6 | | 5a-1+a=11 | | 4a+9=25 | | -5+x=-17 | | 2(6c-2)= | | m=3+5 | | n-30=17 | | j*23*10=5290 | | x+8=-13 | | 4x^2-5x-21=0 | | -10=x+5 | | 20-4*f*10=950 | | 4+7=a | | 36x-2+25= | | 6x+5(x-2)=34 | | 25x=20+15 | | 5y-7x=1 | | 8(4-8)=2a |